EFFECT OF HIBISCUS SABDARIFFA LINN ON IL-6 AND TNF- α LEVELS IN OVERTRAINED RAT HEART - SANTOSO, DEWI IRAWATI SOERIA; YUNITA, SRI; PARAMITA, NURUL; ANDRAINI, TRINOVITA; KARTINAH, NENG TINE; BAYANI, GUSHAN FAHMI EL; ILYAS, ERMITA I. IBRAHIM (International Journal of Applied Pharmaceutics, 2019)
Objective: This study aims to determine the effect of Hibiscus sabdariffa Linn. (HSL) administration on the interleukin-6 (IL-6) and tumor necrosis factor α (TNF-α) levels in rat heart. Overtraining was proven to increase the IL-6 and TNF-α levels in the blood, and HSL had anti-inflammatory and anti-oxidant properties. However, no studies have been conducted on the effect of methanolic extract of HSL administration on the IL-6 and TNF-α levels in overtrained rat heart. Methods: This study used 25 male adult Wistar rats aged 8–10 w and weighing 200–250 g. The rats were randomly divided into five groups: control (C), control H. sabdariffa Linn (C+HSL), overtraining (OT), overtraining H. sabdariffa Linn (OT+HSL), and aerobic (A). Treatment was given 5 times a week for 11 w. At the end of the study, the IL-6 and TNF-α levels were measured using a standard ELISA kit. Results: IL-6 and TNF-α levels in the heart were the highest in the overtraining group. The group that received HSL administration showed the lowest TNF-α and IL-6 levels. Conclusion: HSL could be a used to protect the heart from an inflammatory state, particularly in an overtraining condition.